Emerging agricultural biotechnologies for sustainable agriculture and food security - Anderson, J.A.; Gipmans, M.; Hurst, S.; Layton, R.; Nehra, N.; Pickett, J.; Shah, D.M.; Souza, T.L.; Tripathi, L. (American Chemical Society, 2016)
As global populations continue to increase, agricultural productivity will be challenged to keep pace without overtaxing important environmental resources. A dynamic and integrated approach will be required to solve global food insecurity and position agriculture on a trajectory toward sustainability. Genetically modified (GM) crops enhanced through modern biotechnology represent an important set of tools that can promote sustainable agriculture and improve food security. Several emerging biotechnology approaches were discussed in a recent symposium organized at the 13th IUPAC International Congress of Pesticide Chemistry meeting in San Francisco, CA, USA. This paper summarizes the innovative research and several of the new and emerging technologies within the field of agricultural biotechnology that were presented during the symposium. This discussion highlights how agricultural biotechnology fits within the context of sustainable agriculture and improved food security and can be used in support of further development and adoption of beneficial GM crops.